Linear plasma device GyM for plasma-material interaction studies - Uccello, Andrea; Bin, William; Bruschi, Alessandro; Causa, Federica; Cremona, Anna; De Angeli, Marco; Farina, Daniela; Gatto, Giuseppe; Gervasini, Gabriele; Ghezzi, Francesco; Gittini, Giuseppe; Granucci, Gustavo; et al. (Frontiers in Physics, 2023)
GyM is a linear plasma device operating at Istituto per la Scienza e Tecnologia dei Plasmi, Consiglio Nazionale delle Ricerche, Milan, with the original aim of studying basic plasma physics, such as turbulent processes. Since 2014, GyM experimental program has been mainly focused on the issue of plasma-material interaction (PMI) for magnetic confinement nuclear fusion applications. GyM consists of a stainless steel vacuum chamber (radius and length of 0.125 m and 2.11 m), a pumping system, a gas injection system, 10 magnetic field coils and two magnetron sources at 2.45 GHz, capable of delivering a total microwave power up to 4.5 kW. Highly reproducible steady-state plasmas of different gas species, at a maximum working pressure of 1E-1 Pa, can be obtained by electron cyclotron resonance heating in the resonance layer at 87.5 mT. Plasmas of GyM have electron and ion temperature ≤15 eV and 0.1 eV, respectively. The electron density is in the range of 1E15 - 1E17 m^-3 and the ion flux is ≤5E20 ions•m^-2•s^-1. Main plasma diagnostics of GyM comprise Langmuir probes, an optical emission spectrometer, a mass spectrometer and a fast camera system equipped with an image intensifier unit. For the purpose of investigating the topic of PMI, GyM is provided with two sample exposure systems. Both are biasable at a negative bias voltage down to -400 V, to tune the energy of the impinging ions. One of them is also equipped with a heating lamp and can reach and sustain a temperature of 990 K for several hours, thus allowing to study the role of sample temperature during the plasma-material interaction. This contribution presents the layout of GyM, the diagnostics, the sample exposure systems and the typical plasma parameters. A brief overview of the main PMI activities carried out so far and a description of future machine upgrades are also given.